'It was easy, it was cheap, go & do it' : a importância do do-it-yourself na cena do rock alternativo em Portugal - Oliveira, Ana (2017)
The DIY approach of musical careers lies in thepremise that music is a unifying pole ofactivities, understood as a set of commercialactivities. The analysis of musical production isbased on a business perspective on creativeworkers and specifically on musicians. Severalauthors have paid special attention to the newindependents, freelancers engaged in a logicof reduction of specialization and promotion ofmultiple skills, diluting the boundaries betweenthe professional and the amateur. Thisemphasis is based on the exercise of socialtheory to revisit one of the fundamental valuesof the punk subculture the DIY ethos. It isabout mobilizing the DIY attitude as a newstandard to promote employability, managingthe uncertainty and precariousness of thisoption in terms of building a professionalcareer. Considering the HAUS project, weintend to explore the relevance of DIY logic andprocedures in the construction andmaintenance of musical careers in alternativerock, considering its impact on the musicaloffer of Lisbon.